Tinjauan Literature Review Produksi Bersih Pada Agroindustri Kelapa di Kabupaten Indragiri Hilir-Riau - Siti Wardah (Program Studi Teknik Industri, 2018)
The potential of coconut plantation in Indragiri Hilir Regency is very potential so that the development of plantations with agro-industry approach is an alternative choice that must be developed, in line with economic and trade development in the globalization period which is very demanding the efficiency and effectiveness of the business. In line with the growth of coconut agro industry needs a study on environmental management. Therefore this study aims to assess the potential of clean production in coconut agro-industry in order to challenge the future agroindustry is able to run in harmony with the environment. The method of this research is a literature review whose data are sourced from various national and international journals of other sources such as Books, reports. The result of the review literature review resulted that there are several alternatives that can be done to produce clean production in integrated coconut agroindustry and feasible to be applied. As a suggestion for further research is still need further development because along the development of new product of coconut so as to get product of coconut agroindustry which is competitive.